Supply Chain Controlling and Human Resource Management: An Evidence from Automotive Industry from Indonesia - Retno Purwani Setyaningrum (International Journal of Supply Chain Management, 2018)
For the better success in the contemporary business environment, it is very much obvious to focus on the supply chain controlling and human resource for the better and improved business performance. The objective of present study is to empirically examine the association between the human resource practices HRP and supply chain controlling SCC from the perspective of automotive industry in the region of Indonesia. For this purpose, various HRP have been considered and a sample of 180 experts with their significant experience in SCM has been considered. Findings of the study have explained the fact that there exists a significant relationship between selected factors of HRP and SC controlling in automotive industry of Indonesia. However, the findings of the study are limited to the sample size and lack of some advance statistical methods of analysis. The practical implication of the study can be viewed from the perspective of HRP and SC controlling for the improved business performance matrix. Such association is very much necessary for the business managers and key decision makers, dealing with the SCM, SC controlling and HRP. In addition, originality/value of the study can be considered in a sense that it has focused on the idea of interdisciplinary field like SC controlling, and human resource management and best practices.